Itu Pengembangan Perangkat Pembelajaran Model Learning Cycle 5E Untuk Meningkatkan Penguasaan Konsep Fisika Peserta Didik - Naf’atuzzahrah Naf’atuzzahrah; Muhammad Taufik; Gunawan Gunawan; Hairunnisyah Sahidu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This development research aims to produce such a product in the form of learning tools with the 5E learning cycle model to improve students' mastery of physics concepts. This type of research is included in Research and Development (R&D) with a 4D model consisting of Define, Design, Development, and Dissemination. The learning device products developed are syllabus, Learning Implementation Plan, Student Worksheets, and Concept Mastery Test Instruments. Data collection techniques used validation sheets. The data on the validity of the learning device was obtained from filling out the validation sheet by the validators and has been analyzed using a Likert scale. The results of the study based on the assessment of the validators showed that the average value of the validity of all learning tools developed was 88.54% and 92.62% with very valid and reliable criteria. The variables tested were mastery of physics concepts through limited trial activities by providing test instruments for mastery of physics concepts in the form of pretest and posttest which were then analyzed using the N-gain test. Then the average result of the N-gain test for mastery of physics concepts on static fluid material is 0.55 with a moderate improvement category. So it can be concluded that the learning device of the 5E learning cycle model is valid and effective to improve the mastery of physics concepts for the students of SMAN 1 Gunungsari.